2017
DOI: 10.1186/s12864-017-4341-y
|View full text |Cite
|
Sign up to set email alerts
|

Cold-responsive miRNAs and their target genes in the wild eggplant species Solanum aculeatissimum

Abstract: BackgroundLow temperature is an important abiotic stress in plant growth and development, especially for thermophilic plants. Eggplants are thermophilic vegetables, although the molecular mechanism of their response to cold stress remains to be elucidated. MicroRNAs (miRNAs) are a class of endogenous small non-coding RNAs that play an essential role during plant development and stress responses. Although the role of many plant miRNAs in facilitating chilling tolerance has been verified, little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 47 publications
(32 reference statements)
2
28
0
Order By: Relevance
“…miRNAs are known to regulate plant growth, development and metabolism by controlling numerous cellular, biological and molecular processes [ 22 , 23 ]. Moreover, miRNAs are also reported to play very crucial regulatory roles in numerous biotic and abiotic stresses, such as drought, salt, heat, cold and CO 2 , and in response to various pathogens in different plants [ 24 , 25 , 26 , 27 ]. Recent studies have also shown that miRNAs perform a very critical role in plant growth and development, and in stress responses during various plant–microbe interactions [ 7 , 17 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are known to regulate plant growth, development and metabolism by controlling numerous cellular, biological and molecular processes [ 22 , 23 ]. Moreover, miRNAs are also reported to play very crucial regulatory roles in numerous biotic and abiotic stresses, such as drought, salt, heat, cold and CO 2 , and in response to various pathogens in different plants [ 24 , 25 , 26 , 27 ]. Recent studies have also shown that miRNAs perform a very critical role in plant growth and development, and in stress responses during various plant–microbe interactions [ 7 , 17 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miRNA is generated by summing the count of aligned reads, and a cutoff of abundance over 2 RPM in at least two libraries is used; fourth, we predict the precursor of the identified miRNA, of which, if there is not a hairpin structure, it will be regarded as pseudo-miRNA. Furthermore, a different expressed analysis of miRNA were also performed by using the method of Expdiff [ 37 ]. Considering the lack of biological replicates and technical duplicates in sequencing, a fold-change (log2) threshold of greater than 1 or less than −1 was considered as an indication of significant change [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Known miRNAs were identified by searching against the miRbase and Rfam reference sRNA database using AASRA software, and novel miRNAs were predicted if they were mapped to the intergenic regions, introns, the reverse repeat sequence of a coding sequence, but not to any other RNAs (Nawrocki et al, 2009;Kozomara and Griffiths-Jones, 2014;Chong et al, 2017;Kalvari et al, 2018). The expression levels of sRNA were calculated using TPM (transcripts per kilobase million; 't Hoen et al, 2008), and differentially expressed sRNAs were screened using ExpDiff (Yang et al, 2017). The false discovery rate (FDR) control method was used to determine the threshold of p-value, and the ratio of TPM was used to calculate the fold change in expression.…”
Section: Microrna Identification Differential Expression and Targetmentioning
confidence: 99%